DOMINASI PRODUK NASIONAL DI SEGMEN PASAR REMAJA SURABAYA: STUDI KASUS MENGENAI PREFERENSI PERILAKU KONSUMEN (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
Abstract The purpose of this study is to analyze the dominance of national products in the Surabaya youth market segment and the factors that influence consumer preferences and behavior in choosing national products over imported products. Using a case study approach with a qualitative descriptive method. Data were collected through participatory observation, in-depth interviews, and documentation, with 18 students of Bhayangkara University Surabaya as research subjects who were selected using purposive sampling techniques based on diverse social and economic backgrounds. The results of the study show that the majority of teenagers prefer national products due to several main factors, namely more affordable prices, adequate quality, and wider product availability in various distribution channels, both physical stores and e-commerce platforms. In addition, nationalism is also a driving factor, where some teenagers feel proud to use domestic products and want to support the local economy. Social media plays an important role in shaping this preference, especially through digital marketing campaigns and local influencer endorsements. Teenagers' consumption patterns for national products are dominated by brand loyalty, recommendations to friends, and positive reviews in online purchases. These findings provide insight for local producers to continue to improve marketing strategies, product innovation, and strengthen brand engagement in order to maintain the dominance of national products in the youth segment. Keywords: National products; Surabaya youth segment; case study; consumer behavioral preferences